Analisis Dampak Defisit Anggaran terhadap Inflasi, Jumlah Uang Beredar, dan Suku Bunga di Indonesia - MAULIDINA, FILDZAH IMAS (Jurnal Ilmiah Mahasiswa FEB, 2016)
The purpose of this research is to observe the impact of a budget deficit on inflation, money supply (M1), and interest rate (BI rate) in Indonesia for the period of 2006-2016.  This research was estimated by Error Correction Model (ECM). The Augmented Dickey-Fuller test showed that the data were stationary  at first difference.  The Engle Granger  co-integration  test also showed that budget deficit had a long run relationship with inflation, money supply (M1) and interest rate (BI rate). The estimation of Error Correction Model, in the short-run, implied that budget deficit had a positive  and significant  impact on money supply (M1). The budget deficit had a positive impact but not significant on inflation and interest rate (BI rate). Keyword:  budget deficit, inflation, money supply (M1), interest rate (BI rate), Error Correction Model (ECM)